Second Language Vocabulary Acquisition: The Effects of Semantic Relatedness, Form Similarity, and Translation Direction. Issue 3 (14th March 2021) - Kemp, Lisa S.; McDonald, Janet L.
Abstract: Characteristics of vocabulary lists as well as study and test translation direction may affect the ease of learning second language (L2) vocabulary. We examined immediate and delayed test performance of first language (L1) English speakers learning a fixed set of L2 vocabulary placed on lists formed by crossing semantic relatedness (unrelated vs. related) with L2 orthographic form similarity (not similar vs. similar). During the study phase, half the participants translated from L2 to L1 and half from L1 to L2; tests were then taken in both directions. Semantic relatedness in the absence of form similarity improved accuracy when the first test taken translated from L2 to L1, and tended to hurt accuracy when the first test taken translated from L1 to L2; it sometimes increased confusion errors. Form similarity usually hurt accuracy and always increased confusion errors. The combination of the L1‐to‐L2 study direction with the optimal semantic and form conditions yielded the best long‐term performance. Abstract :